Effect of Serum Osmolarity on Prognosis of Traumatic Brain Injury - Banskota, Narendra Prasad; Malla, Sibika; KC, Rupak (Journal of Nepalgunj Medical College, 2022)
Introduction: Road traffic accident has been a significant cause of mortality in today’s fast paced world. Metabolic and intracranial parameters have affected the outcome of traumatic brain injury. Countless analysis on biomechanical injury and tissue damage has substantiated additional treatment strategies. Laboratory values have been less investigated to predict the outcome of brain injury. Aims: This study was done to find out the association between the serum osmolarity with severity of head injury and the outcome in traumatic brain injury. Methods: This study was conducted at Department of Neurosurgery, Nepalgunj Medical college, Kohalpur, Banke from July 2020 to June 2021. 106 patients were included in the study. Clinical profile of the patients and calculated plasma osmolarity were monitored daily. Results: 106 patients were enrolled with mean age of 39±18.6 and male study population being on the higher side. 62(58.49%) patients with Traumatic Brain Injury accounted for road traffic accident with mild head injury as the commonest presentation. In about 40.57% of the patients osmolarity ranged between 285 to 295 milliosmole/ litre with mean osmolarity of 290.99±10.60. There was no significant association between severity of head injury and serum osmolarity (p value=0.45). Conclusion: There is no association between the severity of head injury with serum osmolarity.